Experiential knowledge, suffering, and vicissitudes of having malaria in the Brazilian Amazon: An ethnographic study - Luciane Machado Freitas de Souza (Canadian Science Publishing, 2017)
This paper focuses on the multiple ways in which people who live along the rivers of the Brazilian Amazon, known as ribeirinhos, experience malaria outside of a clinical setting. It describes the local understanding of malaria, strategies to distinguish the illness from other febrile sicknesses, challenges for detecting the disease through biomedical diagnosis methods, and vicissitudes of having malaria. It draws on cases from ribeirinhos from a peri-urban community of Manaus and a rural community from Careiro, State of Amazonas, Brazil. Although malaria is biomedically characterized by the pathogens causing the disease, ribeirinhos have developed other standards to define malaria, including the intensity of the symptoms, the interval between the infections, and the types of medications dispensed to them. In the riverine communities studied, the etiology of malaria includes mosquitoes, microbes, water, wind, sun, and person-to-person transmission. Symptoms of malaria were found to overlap with other febrile sicknesses; hence, ribeirinhos developed skills to monitor how a malaise unfolds in their bodies. Experiential knowledge plays a key role in the early detection of malaria. Individuals who have no previous experience with malaria were found to spend more time seeking health care. Equally important, ribeirinhos perceive that malaria is part of the landscape they inhabit.